Pengaruh Kualitas Sumber Daya Manusia, Kepuasan Kerja dan Komitmen Kerja terhadap Kinerja Karyawan BPRS Mitra Mentari Sejahtera Ponorogo - An Nihaya, Zuhria; Candra Febrilyantri (Falahiya: Journal of Islamic Banking and Finance, 2024)
Introduction: This research aims to find out and then test and analyze the influence of human resource quality, job satisfaction, and work commitment on the performance of BPRS Mitra Mentari Sejahtera Ponorogo employees. This research uses quantitative methods, by distributing questionnaires to 55 BPRS Mitra Mentari Sejahtera Ponorogo employees as a data collection method. Data analysis was carried out by carrying out validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F test, and coefficient of determination, which were processed using SPSS Statistics 23. The results of this research based on the t-test showed that the variables human resource quality and satisfaction work have a positive and significant effect. In contrast, the work commitment variable does not affect the performance of BPRS Mitra Mentari Sejahtera Ponorogo employees